Virtual integration as a predictor for product innovation: A preliminary insight - Dadriyansyah, Geraldy; Ibrahim, Amlus (2010)
The intense competition in manufacturing industry has forced manufacturing firms to switch their product development approach from traditional to concurrent engineering in order to stay competitive in term of product differentiation and innovation. In order to support concurrent engineering practice, both internal and external participants contributing to product development should be located into close proximity; therefore physical integration of team becomes the key enabler of concurrent engineering. However, as the paradigm has been shifted from adopting “centralized integrated product development”, physical integration is no longer efficient and should be replaced by virtual integration. This conceptual paper intends to explore ways in which virtual integration of internal and external constituents would contribute to product innovation. Concurrent engineering represents the internal constituents, while external constituent is reflected by customer involvement. Based on past literatures in the related field, some prepositions are generated to highlight the implications of virtual integration on product innovation.